Exploring the influence of artificial intelligence on the complexity of landing page anatomy - Borovynska, Y.; Vovk, O. (My University, 2024)
Landing pages serve as digital gateways, crucial for engaging users and driv-ing conversions in the online realm. Understanding the intricate components that comprise these pages is essential for crafting effective online experienc-es. In this article, the anatomy of landing pages and the capabilities of artificial intelligence (AI) in constructing these pivotal digital assets will be explored, focusing particularly on the platform Framer AI.
Keywords: artificial intelligence; landing page anatomy